From crisis to normal: Science teachers’ distance education experiences during COVID-19 and the transition back to face-to-face education - Toğantemur, Seher; Yıldırım, Pelin; Keçeci, Gonca (Anadolu Üniversitesi, 2025)
The pandemic process has accelerated digitalization in education and transformed teaching methods. This study aims to examine science teachers' distance education experiences during the COVID-19 period and their views on the transition to face-to-face education. Conducted between 2020 and 2023, this phenomenological study involved 30 science teachers working in schools affiliated with the Ministry of National Education (MoNE) in the Eastern and Southeastern Anatolia regions of Turkey. Data were collected through semi-structured interviews and analyzed using content analysis. The findings indicate that the use of digital tools in distance education was limited due to infrastructure deficiencies and student access issues. Furthermore, low student participation and readiness gaps negatively affected face-to-face education. While online assessment methods faced reliability issues, face-to-face education preferred more controlled assessment processes. It was found that students' technology addiction increased, and the missing topics needed to be addressed; educational model preferences varied by students' readiness levels and geographic conditions. The study recommends integrating digital tools, strengthening infrastructure investments, and adopting flexible education models to enhance educational effectiveness.
Keywords: Other Fields of Education (Other); Alan Eğitimleri (Diğer)